Antibacterial Soap from Extract Spent Coffee Grounds using Microwave-assisted Extract Against Staphylococcus aureus - Juli Novita Sari; Marina Wulandari Nasution; Agung Pratama (Journal of Chemical Natural Resources, 2025)
This study investigates the application of Microwave-Assisted Extraction (MAE) to extract bioactive components from spent coffee grounds (SCG), enhancing the antibacterial properties of transparent soap. Spent coffee grounds, usually regarded as waste, include phenolics, alkaloids, flavonoids, and tannins which demonstrate potent antibacterial properties against Gram-positive bacteria such as Staphylococcus aureus. MAE effectively extracts these useful compounds using ethanol as a solvent, therefore improving the antibacterial power of the soap. Unlike the soap free of the extract, the inclusion of 3% spent coffee ground extract generated an inhibitory zone of 9.16 mm. The soap base is produced using the saponification process with palm oil and sodium hydroxide. The research additionally encompasses pH analysis, foam properties, and evaluations of client preferences. This research highlights the efficiency of MAE in upcycling coffee waste into a functional and sustainable product, offering enhanced antibacterial properties while contributing to waste reduction in personal care products.